PERAN GURU PAI DALAM MEMBENTUK AKHLAK SISWA DI SMP MUHAMMADIYAH 15 AMBULU - Aminullah, Achmad (Cendikia: Jurnal Pendidikan dan Pengajaran, 2023)
The formation of students’ morals at school can be realized with several supporting factors, one of these supporting factors is the involvement of the role of Islamic religious education teachers in it, therefore teachers are required to provide role models or good examples for their students. The role of Islamic religious education teachers in shaping students’ morals at school has quite a big role, including as educators, tutors, mentors, role models and evaluators. The aim of this research is to determine the role of Islamic Religious Education teachers in shaping student morals at Muhammadiyah 15 Ambulu junior high school. The type of research used in this research is a descriptive qualitative research method with data collection techniques, namely observation, interviews and documentation. The research subjects in this study were 10 people, including 1 Islamic religious education teacher and 9 students from delegates from each class. The results of the research, which are the results of interviews with teachers and several students as well as the results of observations and documentation in schools, show that teachers play a very important role in shaping students’ morals, act as educators in the school, teachers have a method of telling stories first so that students can understand the material well, then in their role as teachers, teachers at school provide lots of practice so that students understand the material more quickly. Then the role as a teacher guide at school because students really need guidance during any activity related to morals, then the role as a role model, teachers at school are very obliged to act as teachers, because it is not enough to only provide material that has been taught in class, but rather Teachers must be able to set a good example for their students, such as being disciplined in going to school, speaking polite words to others. Then finally, the role as an evaluator, teachers at school are also very obliged to play the role of evaluators, apart from this, when at home parents must also play an important role in being evaluators for their children.